2017
DOI: 10.1093/ndt/gfw417
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide multicentre kidney biopsy study of Japanese patients with type 2 diabetes

Abstract: This nationwide study on kidney biopsy of 600 cases with type 2 diabetes revealed that pathologic findings (presence of nodular lesions, exudative lesions and mesangiolysis) were strong predictors of kidney events in low-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 20 publications
3
59
0
Order By: Relevance
“…Back in the early 2000s, a biopsy study done in patients with type 1 diabetes showed that typical glomerular features associated with diabetic nephropathy (diabetic glomerulopathy) are often observed in nonproteinuric diabetic kidney disease, although this study did not deeply investigate interstitial and arterial features [18]. Meanwhile, after 2010, biopsy studies in patients with type 2 diabetes showed that typical glomerular features associated with diabetic nephropathy (diabetic glomerulopathy) are less frequently observed in nonproteinuric diabetic kidney disease, although findings of interstitial and arterial features changed depending on the study [19][20][21].…”
Section: Pathology Of Nonproteinuric Diabetic Kidney Diseasementioning
confidence: 88%
See 2 more Smart Citations
“…Back in the early 2000s, a biopsy study done in patients with type 1 diabetes showed that typical glomerular features associated with diabetic nephropathy (diabetic glomerulopathy) are often observed in nonproteinuric diabetic kidney disease, although this study did not deeply investigate interstitial and arterial features [18]. Meanwhile, after 2010, biopsy studies in patients with type 2 diabetes showed that typical glomerular features associated with diabetic nephropathy (diabetic glomerulopathy) are less frequently observed in nonproteinuric diabetic kidney disease, although findings of interstitial and arterial features changed depending on the study [19][20][21].…”
Section: Pathology Of Nonproteinuric Diabetic Kidney Diseasementioning
confidence: 88%
“…Exploration of biomarkers apart from level of albuminuria may elucidate a mechanism of progression of nonproteinuric diabetic kidney disease. For example, an analysis of a nationwide biopsy-based cohort in Japan with a thorough glomerular investigation showed that diffuse lesions, polar vasculosis and subendothelial space widening predict the prognosis of advanced CKD even in the absence of proteinuria [21]. Notably, the subendothelial space widening also provides prognostic value on predicting CVD events in patients with nonproteinuria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesangiolysis or double contours of basement membranes were also regarded as histologic findings of TMA in the kidney [22]. Because each histologic finding was also observed in various conditions, such as intraluminal microthrombi in disseminated intravascular coagulation [25], fibrinoid necrosis in various vasculitis [26], and mesangiolysis and double contours of the basement membranes in diabetic nephropathy [27], a combination of histologic findings was required for the diagnosis of TA-TMA. Sequential histologic findings, such as from endothelial cell separation through a widening of the subendothelial space to an intraluminal fibrin in the subendothelial space, directly reflect endothelial injury, and such findings are considered the characteristics of TMA.…”
Section: Autopsy Reviewmentioning
confidence: 99%
“…The severity of the diffuse lesions in the glomeruli was scored from 0 to 4 according to the description by Gellman et al (score 0, all glomeruli appear normal; score 1, local lesions present within each glomerulus and focal lesions present within the kidney; score 2, diffuse mesangial thickening within the glomerulus and generalized throughout the kidney; and score 3, narrowed capillary lumina and local obliteration) 3,12 . Nodular lesion, exudative lesion and mesangiolysis were defined as the presence or absence in each specimen 3,13 . The severity of interstitial fibrosis and tubular atrophy (IFTA) was scored from 0 to 3 according to the description by Tervaert et al (score 0, no IFTA; score 1, <25%; score 2, 25-50%; score 3, >50%) 2,3 .…”
Section: Pathological Examinationsmentioning
confidence: 99%